Studi komparatif empat model propagasi empiris dalam ruangan untuk jaringan nirkabel kampus - Fransiska Sisilia Mukti (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2019)
Propagation is one of the important factors to understand in wireless communication systems. Prediction of the value of propagation, especially for closed areas, is very necessary to determine success in building wireless networks. Various kinds of propagation modeling were developed to find the best approach to calculate the value of signal losses. A comparative study of 4 types of empirical propagation modeling was made to provide the most suitable propagation modeling analysis for campus wireless networks. The ITU-R model (P.1238) provides predictive results that are closest to the actual data in the field, with a relative error rate of 16.381%.